Entrepreneurship education: Process, method, or both? - Dianne H. B. Welsh; William L. Tullar; Hamid R. Nemati (Journal of Innovation & Knowledge (JIK), 2016)
Transformative changes are happening in Higher Education Institutions worldwide in entrepreneurship education. These changes are conceptual as well as technological due to the upheaval in the global, social, political, and technological environment. We argue that the process theory of Alfred North Whitehead best explains why entrepreneurship education does not always have the same results on our students in the classroom and after they graduate. In the education of entrepreneurs, we hold that it is change that is the cornerstone of reality-our entrepreneurship students are in the process of becoming something they previously were not. Implications and comparisons of the process theory applied to entrepreneurship education are discussed.
Keywords: M00; M1; 650; Entrepreneurship education; Process approach; Experiential education